Further evidence for heredity of pterygium. (1st October 2016) - Romano, Vito; Steger, Bernhard; Kovacova, Adriana; Kaye, Stephen B.; Willoughby, Colin E.
ABSTRACT: Epidemiological reports strongly indicate that pterygium is an ophthalmoheliosis: a sun-related eye disease. Familial occurrence of pterygium is rare but supports the concept that heredity may predispose the conjunctiva to react abnormally to atmospheric-environmental stimuli. We describe a two generation Caucasian family of five members from the United Kingdom, four of whom developed pterygia in early adulthood with autosomal dominant inheritance. The present report confirms the significance of heredity in the pathogenesis of pterygium. Understanding the genetic basis of pterygium pathogenesis is clinically relevant, particularly in the management of patients who develop recurrent and aggressive pterygia at younger ages.